2016
DOI: 10.1007/s10762-016-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Wide Patch Antenna Array Design at 60 GHz Band for Remote Vital Sign Monitoring with Doppler Radar Principle

Abstract: In this paper, ultra-wide patch antenna arrays have been presented at 60 GHz band (57.24-65.88 GHz) with improved gain and beam-width capabilities for remote detection of respiration and heart beat rate of a person with Doppler radar principle. The antennas measured and simulation results showed close agreement. The breathing rate (BR) and heart rate (HR) of a 31-year-old man have been accurately detected from various distances ranging from 5 to 200 cm with both single-antenna and dual-antenna operations. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…However, some drawbacks were identified. In [23], a test was performed to evaluate the system performance, using a single antenna or two separate antennas for TX and RX. Results showed that a single antenna has good accuracy in vital signs' detection, considering a short-range.…”
Section: Single Antenna For Tx/rxmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some drawbacks were identified. In [23], a test was performed to evaluate the system performance, using a single antenna or two separate antennas for TX and RX. Results showed that a single antenna has good accuracy in vital signs' detection, considering a short-range.…”
Section: Single Antenna For Tx/rxmentioning
confidence: 99%
“…In [23], the authors carefully selected the microstrip type of antenna for their experiments. Apart from having an acceptable gain, microstrip antennas can also be embedded on chip devices, which reduces the total size of the system and use a low-cost fabrication process.…”
Section: Single Antenna For Tx/rxmentioning
confidence: 99%
“…The Doppler effect is an active noncontact method that can detect subtle chest movements due to cardiorespiratory activity. In this method, vital signs are extracted using a Doppler radar [19,20], or laser sensors [21] as well as digital signal processing (DSP) techniques [22] where the phase shift between the transmitted waves and the reflected received waves from a region of interest (ROI) are calculated. There are three types of Doppler-based methods-Doppler with electromagnetics [23,24], lasers [25,26], and ultrasonics [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In the modern point to point wireless communications, it is very common to enhance the gain of microstrip antennas by constituting arrays of multiple patch elements due to the simplicity and cost effectiveness of this approach [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, at microwave and lower frequencies (<30GHz) this technique is limited by the exceptionally large antenna size acquired for high gain (>20dBi) arrays [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, at microwave and lower frequencies (<30GHz) this technique is limited by the exceptionally large antenna size acquired for high gain (>20dBi) arrays [6]. On the other hand, at mm-wave frequencies high gain MPAAs can fit within a small footprint due to the small form factor [7][8][9][10][11][12][13][14][15]. However, at mm-wave frequencies this approach is restricted by the declined antenna efficiency and gain due to the substantial power losses commenced by the extended feeding line network which is vital to deliver matched electrical signal to each of the radiating elements [1][2].…”
Section: Introductionmentioning
confidence: 99%